Effects of Human Capital and Social Capital on Dropping Out of High School in the South - Mark H. Smith; Lionel J. Beaulieu; Glenn D. Israel (Journal of Research in Rural Education, 1991)
This paper assesses the effects of human capital and social capital on the probability of a person dropping out of high school, using the High School and Beyond data set. Utilizing logistic regressi~n, predicted dropout rates are uncovered for students whose families and communities differ in human and social capital, controllmg for financial capital, race, ethnicity, and rural-urban residence. The effects of human and social capital variables combine to make substantial differences in predicted dropout rates.